1992
DOI: 10.1039/c39920001608
|View full text |Cite
|
Sign up to set email alerts
|

The photoaddition of enaminoketonatoboron difluorides with trans-stilbene

Abstract: The photochemical reactions of enaminoketonatoboron difluorides 1 with trans-stilbene gives cyclobutanes 2 and J. CHEM. SOC., CHEM. COMMUN., 1992 ~ azetidines 3 in a regio-and stereo-specific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…BF 2 (Ph,H,Ph Ph ): A mixture of H(Ph,H,Ph Ph ) (1.9 g, 6.5 mmol) and BF 3 · OEt 2 (0.93 g, 6.5 mmol) afforded 2.2 g (97 % yield) of BF 2 (Ph,H,Ph Ph )9a as a yellow solid; m.p. 195.0–196.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…BF 2 (Ph,H,Ph Ph ): A mixture of H(Ph,H,Ph Ph ) (1.9 g, 6.5 mmol) and BF 3 · OEt 2 (0.93 g, 6.5 mmol) afforded 2.2 g (97 % yield) of BF 2 (Ph,H,Ph Ph )9a as a yellow solid; m.p. 195.0–196.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Melting points are determined on a X-4 micro melting instrument and the thermometer is uncorrected. The 1 H NMR (400 MHz), 13 C NMR (100 MHz), 11 B NMR (128 MHz) and 19 F NMR (376 MHz) spectra are obtained on a Bruker Avance II DMX400 spectrometer using DMSO-d 6 as the solvent. The 1 H NMR and 13 C NMR experiments are carried out using trimethylsilane as the internal standard while the 11 B NMR and 19 F NMR spectra are recorded using BF 3 OEt (0 ppm) and CF 3 COOH (76.5 ppm) as the external standards, respectively.…”
Section: Instrumentation and Materialsmentioning
confidence: 99%
“…There are two main types of these complexes, classified as N, N double-dentate and O, O double-dentate compounds, BODIPY (boradipyrromethene) [1][2][3][4] and 1,3,2-dioxaborine [5][6][7][8] are their corresponding representatives. However, there are few reports [9][10][11] available on the generation of difluoroboron complexes with N, O double-dentate ligands. Although we have reported [12] the synthesis and X-ray crystallography of a difluoroboron complex containing the N, O double-dentate ligand derived from a Schiff 0 s base of salicyaldehyde, its poor quantum yield and low fluorescence intensity compelled us to explore other approaches to such compounds.…”
Section: Introductionmentioning
confidence: 97%
“…The enaminoketonatoboron difluorides (1a-c) were prepared from borontrifluoride methyletherate and the 1,3-enaminoketones obtained by the method described by Tokutomi and Hayashi 3 and by us. 5 Photoaddition reactions…”
Section: Methodsmentioning
confidence: 99%
“…Hence, following the enhanced reactivity of 1,3-diketone BF 2 complexes toward olefins as demonstrated by Chow and Cheng, 4 we prepared a number of enaminoketonatoboron difluorides (complexes, 1a-c) by reaction with boron trifluoride. In earlier work we showed that the photoreactions of the complexes 1a-c with cyclic olefins, besides resulting in some complex olefin adducts, 5 yielded two photoproducts (2a-c and 3b, c) as byproducts. These latter compounds are also produced by photochemical reaction of the complex alone in solvent (hexane, benzene, etc.)…”
mentioning
confidence: 96%